2013
DOI: 10.1038/mi.2012.71
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of type 1 diabetes through infection with an intestinal nematode parasite requires IL-10 in the absence of a Th2-type response

Abstract: Helminth infection can prevent type 1 diabetes (T1D); however, the regulatory mechanisms inhibiting disease remain largely undefined. In these studies, nonobese diabetic (NOD) IL-4(-/-) mice were infected with the strictly enteric nematode parasite, Heligmosomoides polygyrus. Short-term infection, 5-7 weeks of age, inhibited T1D onset, as late as 40 weeks of age. CD4(+) T-cell STAT6 phosphorylation was inhibited, while suppressed signal transducer and activator of transcription 1 phosphorylation was sustained,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 53 publications
2
56
0
Order By: Relevance
“…It was shown that infection with Schistosoma mansoni could prevent diabetes onset in NOD mice [19]. Other studies confirmed the potent effect of other helminth infections on T1D in NOD mice including Trichinella spiralis, Heligmosomoides polygyrus [20,21]. Protection was associated with an augmented Th2 response, increased generation of regulatory T (Treg) cells, production of IL-10 by T and B cells and reduction in infiltrating CD8 + T cells in the pancreas; all of which would have the potential to inhibit diabetes onset.…”
Section: Introductionsupporting
confidence: 52%
“…It was shown that infection with Schistosoma mansoni could prevent diabetes onset in NOD mice [19]. Other studies confirmed the potent effect of other helminth infections on T1D in NOD mice including Trichinella spiralis, Heligmosomoides polygyrus [20,21]. Protection was associated with an augmented Th2 response, increased generation of regulatory T (Treg) cells, production of IL-10 by T and B cells and reduction in infiltrating CD8 + T cells in the pancreas; all of which would have the potential to inhibit diabetes onset.…”
Section: Introductionsupporting
confidence: 52%
“…At odds with data from short-term Th2 clones [5], long-term cultured Th2 clones derived from the same TCR transgenic animals have the capacity to induce diabetes, and could even enhance the ability of Th1 cells to cause disease [25]. The effect of helminth products on the immune response was also shown to be more complex than anticipated originally, with effects on regulatory T cells and innate lymphoid cells [11], and it is now clear that helminth infection can protect from diabetes without necessarily invoking Th2 differentiation [26,27].…”
Section: Evidence Against the Th1 Paradigmmentioning
confidence: 99%
“…They require multiple interactions between innate and adaptive immune cells. This complexity was demonstrated in studies using IL-4-deficient NOD mice that failed to develop a Th2 shift in response to H. polygyrus or L. sigmodontis, but still were protected from diabetes by the infection [67,68]. On the other hand, the expansion of regulatory cell populations (Foxp3 + -expressing and/or IL-10-secreting T cells) induced by helminth infections was shown to be dispensable for diabetes prevention in IL-4-competent NOD mice infected with H. polygyrus [45].…”
Section: Mechanisms Of Helminth-mediated Diabetes Protectionmentioning
confidence: 99%